(3GdQhVI GdZfGA aj CUhd GdZfGAs
(3ChdgG (B:s
(3hHYO aEfg deG cGf GdZfGA hddSeGY jUHh Gdjg cd dHjH hVYJ gPG GdeLehY eTJedkG Ydi CUhd CdMGf hCUhGJ haQhY hehTMGJ s
(3BNQgG (B:s
(3ef cdGe GdEeGe GHf GdaGQV GQMehG ef VGbh HghGce hHbhG YfO QhVJi HGdMLhf hGSeMhG HGdePGQ ddQhM GPG ai fYje CfJe RQJehfi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B53 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs